PENGARUH PEMBERIAN BERBAGAI DOSIS LIMBAH PADAT KELAPA SAWIT (SLUDGE) TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN PADI (Oryza sativa. L) DENGAN METODE JAJAR LEGOWO 4:1 - Chairil Ezward; Dadang Kurniawan; Haris Susanto (Universitas Muara Bungo, 2019)
This research has been conducted in UPT. Department of Food Crops Sentajo. The purpose of this study to know the effect of varying doses of palm solid waste (sludge) on the growth and yield of rice (Oryza sativa. L) method Legowo row 4: 1. The method used was a randomized block design (RAK) Non Factorial ie the dose palm solid waste (sludge) consists dai 4 treatments and 3 replications. Treatment S0 = without treatment, S1 = 1.2 kg / plot, S2 = 2.4 kg / plot, S3 = 3.6 kg / plot, each experimental unit consisted of 24 plant samples. The data were statistically analyzed, with a further test significant difference (HSD) at 5% level. Based on the results, it can be concluded that pemberin various doses of solid waste palm method Legowo row 4: 1 gives a significant effect on all observations. The best treatment there in treatment S3 (30 ton / ha) with plant height (84.28 cm), the age of flowers (78.53 days), harvesting (108.61 days), number of tillers (25.53 rod), the number of productive tillers (21.17 bars) and dry grain weight (628 g / plot). Keywords : Rice (oryza sativa.L), solid waste oil palm (sludge), legowo method a 4 :